Recurrence of occult hepatitis B virus infection in a recipient of a liver transplant for HCV-related cirrhosis: full length genome, mutations analysis and literature review - Bajjou, Tahar; Tagajdid, Mohammed Rida; Elkochri, Safae; Abi, Rachid; Touil, Nadia; Rahoui, Jalila; Kandoussi, Fatima Zahra; Sakhsoukh, Yassine; annaz, Hicham El; Mrani, Saad (International Journal of Research in Medical Sciences, 2017)
The outcome of liver transplant recipients in HCV chronic carriers with Anti-HBc only concerning occult HBV infection is unknown. We report here the case of a patient who underwent liver transplantation (LT) for cirrhosis post chronic hepatitis C who received an allograft from a donor with no marker of hepatitis B infection. After LT, HBV DNA was detected in the serum in the absence of HBsAg while HCV RNA remained negative. To determine the origin of this occult HBV infection, we retrospectively examined stored serum and liver tissue, pre and post-transplantation, for HBV DNA by PCR. A stored liver biopsy of the donor before transplantation was also tested. HBV DNA was detected in the pre-transplant liver but not in the donor liver. HBV viral load quantified by real time PCR after LT ranged from about 102 to 5x103 HBV DNA copies/mg of liver, while in sera, concentrations ranged from 102 to 3x103 HBV DNA copies/ml. All PCR products in the S gene from liver and sera were sequenced. Analysis of sequences showed the presence of an HBV strain genotype D. The nucleotide homology between the patient’s HBV strains before and after LT was 96 % across the analyzed regions. Full length HBV genomes were amplified from the sera using Rolling Circle Amplification and then sequenced. Analysis of sequences confirmed the genotype D, but did not show obvious mutations that could contribute to HBsAg seronegativity and low HBV viral replication. Factors leading to occult HBV infection are still unclear, but it is well establish that occult HBV infection is frequent in HCV patients. This underlines the role of extra hepatic sites for HBV replication, potentially lymphocytes acting as “reservoirs”.